Cognitive dissonance, critical theory and political reasoning - Stein Lubrano, S (2023)
Critical theorists have long wrestled with whether and how to provide a theory of “false consciousness” to explain why the oppressed hold beliefs aligned with their own oppression. They often either eschew psychological explanations or rely solely on psychoanalysis. I suggest cognitive dissonance theory can also prove an important resource for understanding failures of political consciousness. Dissonance theory helps explain how subjects are “interpellated” into harmful ideologies through their actions, and how new action-possibilities, as well as the support of others, can help subjects “escape” harmful ideologies. Dissonance theory can also enrich the works of the first, second, and third generation of the Frankfurt School of critical theory. It provides clarity in debates between Theodor Adorno, Herbert Marcuse, and Erich Fromm about the role of the ego in political consciousness, without relying on Freudian theories and their often-implied patriarchal family structures. Dissonance theory demonstrates the role of a sense of self in subjects’ ideological beliefs, demonstrating that an attachment to an individual fixed sense of self may leave subjects too defended psychologically to escape harmful ideologies. This is especially relevant as subjects are further atomised under neoliberalism. Dissonance theory can also provide an alternative to the developmental psychology employed by Jürgen Habermas and Axel Honneth. It can explain why subjects arrive at poor political conclusions without turning to rigid developmental hierarchies or possibly-unwarranted normative claims. Ultimately, “false consciousness” can be defined carefully as a set of beliefs that inhibit subjects from recognising their possibilities for action, then dissonance theory can be used to understand how subjects often hold tightly to this kind of false consciousness. With this approach critical theorists can theorise paths to emancipatory consciousness and aid social movements. Furthermore, critical theorists should explore other areas of cognitive science that may also prove fruitful in understanding political consciousness.